2011
DOI: 10.1136/bmjqs.2009.038604
|View full text |Cite
|
Sign up to set email alerts
|

Three success factors for continual improvement in healthcare: an analysis of the reports of improvement team members

Abstract: A pattern of three success factors for CQI emerges: (1) continuous and reliable information, including measurement, about best and current practice; (2) engagement of everybody in all phases of the improvement work: the patient and family, the leadership, the professional environment and the staff; and (3) an infrastructure based on improvement knowledge, with multidisciplinary teams, available coaching, learning systems and sustainability systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
69
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 47 publications
6
69
0
1
Order By: Relevance
“…This is in accordance with Brandrud et al ,30 who found three success factors for continuous quality improvement; continuous and reliable information, involvement by all, and an infrastructure based on improvements in knowledge.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with Brandrud et al ,30 who found three success factors for continuous quality improvement; continuous and reliable information, involvement by all, and an infrastructure based on improvements in knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…This was also the team members’ view, considering that the most important function of the GTT method was the identification of AEs. In line with Brandrud et al ,30 they developed new knowledge that appeared to be useful locally.…”
Section: Discussionmentioning
confidence: 62%
“…Further research is needed to further unpack the "black box" of improvement. 12,13 Still, the 7 actions promoting QIC success that emerged in this study and similar in other studies 43,44 can support teams and leaders who are planning new QICs.…”
Section: Discussionmentioning
confidence: 50%
“…These include: cross-site and local learning activities (e.g., staff education, PDSAs, team effectiveness) (31, 47, 5355), local leadership support, sites’ ability to address common implementation barriers, expert support, ongoing data collection, and the visibility of local changes achieved through QI methods (3, 33, 47, 5659). Additionally, there is a great need to continue to examine the costs associated with LCs and the incremental cost-benefit of using this approach, compared to traditional developer trainings and other QI methods.…”
Section: Discussionmentioning
confidence: 99%